Study of rain rate and rain attenuation for finding the optimum frequency uses by maritime radar at Malaysia / Muhammad Rezza Alui - Alui, Muhammad Rezza (2012)
Rain attenuation has long been recognized as the main source of atmospheric attenuation in terrestrial and satellite links. There are many rain attenuation prediction models that are exist in the world. If the overseas model is applied to the design and operation of the domestic system such like radar or satellite, it can causes big error compared with real attenuation quantity in domestic environment. To estimate it more correctly, it should be developed appropriate model at domestic environment. This proposal report looks the comparison between the existing rain attenuation models with the measured model that is conducted at the domestic area. This study proposes which existing rain attenuation model is applicable to use at the domestic area according to the data from the measured model and apply it to indentify the optimum frequency use in the domestic area.